Assessment and interpretation of teachers' attitudes towards students with disabilities - Solís, Patricia; Pedrosa, Ignacio; Mateos-Fernández, Luz-Maria (Cultura y Educación, 2019)
The process of including students with disabilities is necessarily influenced by teachers' attitudes towards them and towards their inclusion in education. After detecting the need to study the attitudes present in preschool and primary and secondary school teachers, this study was proposed as it was decided that an analysis of such attitudes could help to develop a better understanding of the current needs of the education system. This study analysed data on attitudes from a total of 175 teachers (29.10% male) working in state schools (50.30%) and semi-private schools in different autonomous communities of the Spanish state. An adapted version of the teacher questionnaire on attitudes towards students with special educational needs arising from disability was used. After analysing the psychometric properties of the questionnaire, further purification of these properties resulted in an assessment instrument comprising 22 items. It is worth highlighting the appraisal that teachers carry out of their training, the existence of resources, as well as their own level of involvement.
Evaluación e interpretación de la actitud del profesorado hacia alumnos con discapacidad
El proceso de inclusión de los alumnos que presentan alguna discapacidad está necesariamente influido por las actitudes de los docentes hacia ellos y hacia su inclusión educativa. Tras detectar la relevancia del estudio de las actitudes presentes en el profesorado de educación infantil, primaria y secundaria se plantea la presente investigación ya que se considera que el análisis de las mismas ayudará a lograr una mayor comprensión de las necesidades propias del sistema educativo actual. En la presente investigación se analizan los datos sobre actitudes provenientes de un total 175 profesores (29.10% hombres) que ejercen tanto en colegios públicos (50.30%) como concertados de diversas comunidades autónomas del estado español. Se ha recurrido a la utilización del cuestionario para profesores de actitudes hacia los alumnos con necesidades educativas especiales derivadas de discapacidad en su versión adaptada. Tras analizar las propiedades psicométricas del cuestionario, la depuración del mismo ha generado un instrumento de evaluación que consta de 22 ítems. Se debe destacar la apreciación realizada por los profesores acerca de su formación y la existencia de recursos además de su propio grado de implicación.
Keywords: evaluation; education; teachers; students; attitudes; disability; evaluación; educación; profesor; alumno; actitudes; discapacidad; JCR; Scopus